Mohammed Ibn Abdel-karim Al-Zammouri and his approach to achieving the Algerian heritage between tradition and renewal - tahri, mhamed (The Algerian Historical Journal, 2026)
The endeavor of this study is to stand on the most important scientific contributions of Muhammed Iin Abdel-Karim Al-Zammouri in the field of grading and editing texts, with an indication of his scientific approach in dealing with manuscript sources in the Medieval and Modern era to know the degree of imitation and renewal of scientific approaches in the science of manuscript verification through selected models. As his works generally came to be in the category of reviving the Arab-Islamic heritage in general and Algerian history in particular, following a scientific approach that combines the tradition of the predecessors and reiterating the progress made in the science of verifying Arabic-Islamic manuscripts, which made his works a testament to his prowess in graduation, control, investigation and publication